Comparison of various sire evaluation methods in a herd of Holstein Friesian cattle - ASWATHANARAYANA, T (The Indian Journal of Animal Reproduction, 2003)
Relative efficiency of the sire evaluation procedures based on minimum standard error of procedures indicated that both BLUP and MCC methods were more appropriate and efficient in estimating the breeding values of sires compared to SDA and CC. The accuracy and efficiency of BLUP and MCC procedures was probably due to their ability to remove the inherent biases in the data which are likely to arise from sampling sire progeny, progeny per sire effect of geographical location, period and season. In general, BLUP procedure was found to be the best in its application due to its consistency and unbiasedness in ranking of sires in comparison to other procedures. The present findings strongly recommend the use of BLUP procedure for evaluating sires under field and farm conditions, since the BLUP procedure had an advantage over MCC, especially in the absence of data on contemporary daughters.